Hubungan Gaya Kelekatan Dengan Self-Efficacy Akademik Siswa SMA Di Jakarta - Sari, Raysita Nilam; Akmal, Sari Zakiah (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2018)
The academic problems of high school students that often happens are ineffective learning method, completion of tasks and exercises, search and use of learning resources, learning difficulties, lack of concentration in learning and other high academic demands. On such problems, the researcher surveyed 30 high school students and the results showed that 60% of 30 high school students have low academic self-efficacy. The factors of academic self-efficacy include family, neighborhood and school. Attachment may affect self-efficacy which is critical to academic success. The research was carried out by distributing the attachment style and academic self-efficacy scale to 247 high school students in Jakarta. The results showed that there was a significant positive relationship between secure attachment style and academic self-efficacy of high school students (r = 0.130 and p = 0.040). In addition there was a significant negative relationship between a fearful-avoidant attachment style attachment and self-efficacy of academic high school students (r = -0, 198 and p = 0.002).